1995
DOI: 10.1097/00005373-199501000-00021
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of the Performance of the Trauma Team Leader

Abstract: This study assessed the performance of the trauma team leader in 50 consecutive trauma resuscitations at Liverpool Hospital over a two-month period. The trauma team consists of intensive care (ICU), emergency, and surgical registrars, three nurses, a wardsman, a radiographer, and a social worker. The team leader position alternates between the ICU and emergency registrar on a fortnightly roster. A panel of specialists experienced in trauma management evaluated 38 aspects of the initial resuscitation. Individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 22 publications
1
58
0
1
Order By: Relevance
“…19 , 20 Some argue that the team should be led by a surgeon, 19,20 while others believe anyone trained in trauma management can provide adequate care, and the team leader should rotate between various specialists. 21,22,23 Interestingly, we find that even though the team leader differs in the French and U.S. systems, mortality remained the same. This has implications for optimal allocation of resources, especially in areas where surgeon availability is low.…”
Section: Discussionmentioning
confidence: 64%
“…19 , 20 Some argue that the team should be led by a surgeon, 19,20 while others believe anyone trained in trauma management can provide adequate care, and the team leader should rotate between various specialists. 21,22,23 Interestingly, we find that even though the team leader differs in the French and U.S. systems, mortality remained the same. This has implications for optimal allocation of resources, especially in areas where surgeon availability is low.…”
Section: Discussionmentioning
confidence: 64%
“…This is due in part to expert groups such as the Institute of Medicine and regulators like the Joint Commission for Accreditation of Health-care Organizations who advocate some type of team training. In addition, research suggests the need for improved teamwork and communication in neonatal intensive care, 2,3,16 emergency departments, 10 the operating room, 17,18 trauma resuscitation [19][20][21] and among residents of all disciplines. 22 Despite this interest and research, two recent reviews concluded that no studies have shown that team training can improve teamwork and the quality of care, 11,12 and a cluster randomized trial of team training for labor and delivery teams did not find significant changes in the process of care or outcome measures.…”
Section: Discussionmentioning
confidence: 99%
“…5 A training course, therefore, has to cover these topics in theory and in practice, as has been shown previously. 9,14 Simultaneously, targeted individual skills and competency training, as the ATLS and similar courses, has to take place in parallel with team training. In Norway, these training modalities are seen as complementary and not competitive.…”
Section: Discussionmentioning
confidence: 99%